MANFAAT PROGRAM SERTIFIKASI PRIMA-3 DAN SLPHT DALAM MENGEMBANGKAN USAHATANI NANAS YANG BERKELANJUTAN DI KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Mariyana Mariyana; Fembriarti Erry Prasmatiwi; Novi Rosanti (Lampung University, 2016)
This research aims to examine the performance of pineapple farming and the benefit of prima-3 certification and SLPHT in developing sustainable pineapple farming in terms of economic, social and environmental. This research compares the practice of pineapple farming management of certified, SLPHT and non-SLPHT farmer. The research location is in Astomulyo Village, Punggur Sub District, Central Lampung District. The sample in this research are 75 farmers that consist 15 certified farmers, 30 SLPHT farmers and 30 non-SLPHT farmers. The benefit of prima-3 certification and SLPHT in economic terms determined by farm income, meanwhile the pineapple quality assuredness, social and environmental terms analyzed using sustainability index. The different test of F test (One Way Anova) and Post Hoc Test LSD is used afterwards to analyze the assessment of pineapple farming. The results show that farm income of the first year to the third year sequentially for certified farmers are Rp57.450.792; Rp136.367.252 and Rp17.330.297, for SLPHT farmers are Rp54.169.465; Rp137.874.183 and Rp19.220.465, and non-SLPHT farmers are Rp55.326.879; Rp127.256.986 and Rp14.798.958. Prima-3 certification program and SLPHT in economic terms that is determined by farm income have not provided benefits, but the assesment result of pineapple farming management towards the increasing of the pineapple quality assuredness have provided benefits. As well as benefits in social and environmental terms showed that there’s significant difference of the practice of pineapple farming management between certified, SLPHT and non-SLPHT farmers. Key words: pineapple, Prima-3 Certification, SLPHT, sustainability